Pengaruh likuiditas,aktivitas, leverage dan ukuran perusahaan terhadap return on assets pada perusahaan manufaktur yang terdaftar di bei tahun 2019-2021 - Oktavia, Martha; Titiek, Suwarti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Return On Asset is a ratio used to measure/show the results (return) on the number of assets used in the company. The preparation of this study aims to examine and analyze the effect of liquidity, activity, leverage and firm size on Return On Assets in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The population used in this study are all manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. This study uses descriptive and quantitative statistical methods. Researchers took samples using purposive sampling. The type of data used in this study is secondary data obtained from financial reports that have been published by the company. The technique in taking the sample is using multiple linear regression. The results of this study indicate that Liquidity (CR), Activity (TATO), Firm Size (SIZE) have a positive effect on Return On Assets. Meanwhile, Leverage (DER) has a negative effect on Return On Assets.